1939
DOI: 10.1037/h0054288
|View full text |Cite
|
Sign up to set email alerts
|

A stimulus-response analysis of anxiety and its role as a reinforcing agent.

Abstract: Within recent decades an important change has taken place in the scientific view of anxiety (fear), 2 its genesis, and its psychological significance. Writing in 1890, William James (6) stoutly supported the then current supposition that anxiety was an instinctive ('idiopathic') reaction to certain objects or situations, which might or might not represent real danger. To the extent that the instinctively given, predetermined objects of anxiety were indeed dangerous, anxiety reactions had biological utility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
218
1
7

Year Published

1949
1949
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 630 publications
(239 citation statements)
references
References 6 publications
(5 reference statements)
8
218
1
7
Order By: Relevance
“…22,23 Habituation, for example, would predict that responses to cancer recurrence may be difficult, but less so than those experienced at the initial diagnosis, and certainly not worse. Many experiences and circumstances would be familiar ones (e.g., disruption of daily routines, immersion in the medical system, knowledge of cancer treatments and the symptoms they produce) and consequently, less distressing.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Habituation, for example, would predict that responses to cancer recurrence may be difficult, but less so than those experienced at the initial diagnosis, and certainly not worse. Many experiences and circumstances would be familiar ones (e.g., disruption of daily routines, immersion in the medical system, knowledge of cancer treatments and the symptoms they produce) and consequently, less distressing.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural avoidance was the first of these to receive much attention in the literature (Mowrer, 1939) as a mechanism by which access to environmental reinforcers, which might usually have alleviated a transient state of depression, becomes restricted, perpetuating a pathologically low mood state. Behavioural Activation therapy (Lewinsohn, Antonuccio, Steinmetz, & Teri, 1984) was developed to correct this loss of positive reinforcement, and to this day shows positive effects on people with depression which some argue are equivalent to the efficacy of more complex cognitive therapy packages (Jacobson & Gortner, 2000).…”
mentioning
confidence: 99%
“…Previous studies have already demonstrated that interoceptive awareness is associated with the intensity of emotional experience (Barrett et al, 2004;Wiens et al, 2000). Moreover, (very) early studies of Mowrer (1939) already indicated that the power of the UR affects the strength of the conditioned response.…”
Section: Discussionmentioning
confidence: 97%